The Modi Factor in the 2019 Lok Sabha Election: How Critical Was It to the BJP Victory?. (December 2019) - Shastri, Sandeep
The BJP victory in the 2019 elections is attributed to a range of factors. This article examines the role of the leadership factor in propelling the BJP to victory in this election. While the Prime Ministerial candidate of the BJP/NDA was clearly the preferred choice, the National Election Study 2019, undertaken by Lokniti–CSDS, indicates that one-thirds of those who supported the BJP would have altered their voting preference if Modi were not to be the Prime Ministerial candidate of the party. The article explores the leadership factor in the 2019 election and concludes that it was a major factor that influenced voter choice.